(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Introduction: Higher Education Institutions are considered as organizations that generate knowledge through the research carried out by their academic staff. Organizational mechanisms such as organizational structure regulate the activities of employees, which in organizational learning theory is called Organizational Structure. Among the questions, what is required to attract and retain research professors? What does it take to increase your productivity? Objective: to demonstrate if there is a relationship between some of the variables of the organizational structure with the scientific productivity of the research professors. Material and method: work carried out in a university in the Mexican southeast, with university professors who carry out research as the target population, for which an instrument of 53 items on a Likert scale, in 5 points, was applied, surveying 304 professors, the The method used was quantitative, not experimental, the linear regression statistical tool was used. Results: It was found that the independent variable Specialization of the Organizational Structure explains 46% of the dependent variable Scientific Productivity, and having an ANOVA sig. less than .05, a linear relationship is demonstrated. Although the Departmentalization variable has a linear relationship with Scientific Productivity, they vary in a negative direction -20.9% Conclusions: The Hierarchy, Centralization and Formalization variables have sig values greater than .05, so it was determined that there is statistical evidence of a linear relationship with the dependent variable.